Pemphigus Vulgaris: Oral Pathologist as Sentinal - Alkananda Sahoo1, Swagatika Panda2, Santosh Subudhi3, Neeta Mohanty4, Debkant Jena5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The word ‘Pemphigus’ has been derived from a Greek term meaning “blister”. Pemphigus vulgaris is a chronicautoimmune vesiculobullous lesion primarily manifesting as intraoral blisters, gradually involving otherparts of the mucous membrane and skin. Though the exact etiology is unknown the lesion is characterizedby the production of autoantibodies directed against the intercellular substances thus categorizing it as anautoimmune disorder. Early diagnosis and management determine the course of the lesion hence dentalpractitioners should be well aware of the clinical features of pemphigus vulgaris as early diagnosis is ofconsiderable value since therapy is simplified when the lesion is confined to the mouth. Here we are reportinga case of a 40 year old female presenting with pain and burning sensation in the left retromolar area alongwith an overview of the disease.